Method for repairing concrete cracks by cementing natural zeolite through microbial mineralization technology
Through microbial mineralization technology combined with natural zeolite particles, the problems of complexity, pollution and high cost of traditional repair methods are solved, and the crack repair effect is achieved with high efficiency, environmental protection and low cost, which significantly improves the durability of the concrete structure.
Patent Information
- Application Number
- CN202510076927.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional concrete crack repair methods have complex operation, high environmental pollution and high cost, and cannot effectively and deeply repair cracks, affecting the durability of the concrete structure.
Microbial mineralization technology is used to combine natural zeolite particles, and the microbial mineralization of Bacillus Pasteuris and cement natural zeolites are deeply repaired, and concrete cracks are enhanced to enhance their bonding ability and density.
In-depth repair of concrete cracks has been achieved, the overall performance and durability of concrete structures have been improved, and the operation is simple, environmentally friendly, low-cost, and cost-effective.
Smart Images

Figure CN119877880A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete crack repairing, and in particular to a method for repairing concrete cracks by utilizing microbial mineralization technology to cement natural zeolite. Background Art
[0002] Traditional reinforced concrete is the most widely used material in the construction industry around the world. Due to its high compressive strength and low tensile strength, microcracks will appear inside and on the surface of its structure during long-term service due to external loads and other reasons. In addition, the stress near the cracks will be redistributed at the cracks due to the obstruction of the cracks, further causing the cracks to continue to expand. The generation and expansion of tiny cracks may cause the mechanical properties, water seepage resistance, anion corrosion resistance, sound insulation, heat insulation, and other properties of concrete to be greatly reduced, greatly shortening the service life of concrete structures. In 2024, my country's concrete usage accounted for more than 50% of the global total. Therefore, the mechanical properties and structural durability problems caused by concrete cracks are particularly prominent in my country, and the cracks have to be repaired and filled to reduce the adverse effects of microcrack expansion.
[0003] Traditional concrete crack repair methods include surface sealing, plugging, structural reinforcement, and carbon fiber packaging, which have been widely used, but these traditional repair methods still have some shortcomings. The surface sealing method cannot penetrate deep into the cracks, and can only prevent the cracks from contacting chloride ions to further expand the steel corrosion. It is not suitable for cracks with obvious water pressure. Chemical methods often use organic chemical materials. On the one hand, some organic materials have certain toxicity and have adverse effects on the environment and human body; on the other hand, there are certain differences in the expansion of organic materials and concrete materials, resulting in poor compatibility between the two. Therefore, researchers began to devote themselves to the study of new materials that are environmentally friendly, low-cost and can effectively repair concrete cracks. Therefore, it is urgent to find a new, efficient and green method for repairing concrete cracks. Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite, which utilizes the microbial mineralization effect of Bacillus pasteurianus and bonded natural zeolite to repair concrete cracks from multiple directions, and has the characteristics of simple operation, green environmental protection and cost saving.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] A method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite comprises the following steps:
[0007] 1) Place a layer of plastic permeable gasket and permeable gauze on the concrete crack, and align the center of the circular grouting nozzle with the concrete crack;
[0008] 2) Glue the grouting nozzle to the concrete interface with waterproof glass glue;
[0009] 3) After the glass glue has dried for 20 to 40 hours, screw the glue injector on the top of the grouting nozzle, and use the pressure of the glue injector to inject the natural zeolite particles into the cracks to fill the cracks;
[0010] 4) Remove the glue injector, connect the peristaltic pump tube to the grouting nozzle, pump in the bacterial solution, wait for 2.5 to 7.5 hours, and then continue to inject the cementing liquid. Then wait for 16 to 22 hours and repeat the grouting process. A total of 3 injections are made.
[0011] As a possible implementation, further, in step 3), the natural zeolite has a particle size of 0.25 to 0.5 mm.
[0012] As a possible implementation manner, further, the binder liquid in step 4) is a mixed solution of urea and calcium acetate of equal concentration and volume, and its concentration is 0.25 mol / L to 1.5 mol / L.
[0013] As a possible implementation, further, the microorganism in the bacterial solution in step 4) is Bacillus pasteurianus, which can induce urea hydrolysis to generate carbonate.
[0014] As a possible implementation mode, further, the method for preparing the bacterial liquid includes:
[0015] a) mixing deionized water, yeast extract, ammonium sulfate, and nickel chloride hexahydrate and stirring uniformly to prepare a microbial culture medium;
[0016] b) adding sodium hydroxide to the microbial culture medium to adjust its pH value to 10-12;
[0017] c) placing the microbial culture medium in an autoclave and cooling it to room temperature after sterilization;
[0018] d) using an inoculation loop to inoculate Bacillus pasteurianus into the sterilized microbial culture medium on a clean bench;
[0019] e) placing the inoculated microbial culture medium in a constant temperature shaking incubator, and shaking and culturing to obtain the bacterial solution.
[0020] As a possible implementation manner, further, in step a), 1000 mL of deionized water, 15-25 g of yeast extract, 10-20 g of ammonium sulfate, and 10-20 μmol of nickel chloride hexahydrate are mixed and uniformly stirred to prepare a microbial culture medium.
[0021] As a possible implementation manner, further, in step c), the microbial culture medium is sterilized at 130±8° C. and 0.11-0.16 MPa for 25-50 min and then cooled to room temperature.
[0022] As a possible implementation manner, further, the microbial culture medium inoculated in step e) is continuously shaken and cultured at 20 to 30° C. and 200 to 230 rpm / min for 20 to 24 hours to obtain the bacterial solution.
[0023] As a possible implementation manner, further, in step 4), the amount of bacterial liquid and cementing liquid pumped in each time is one third of the fracture volume.
[0024] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0025] 1) The present invention can effectively fill the pores in the zeolite particles by combining the method of pre-filling natural zeolite particles with microbial mineralization technology, improve its overall bonding ability, increase the overall density inside the concrete cracks, and thus improve the overall performance and durability of the concrete structure.
[0026] 2) The present invention utilizes microbial mineralization technology to bond natural zeolite to repair concrete cracks. Compared with traditional concrete repair methods, it can repair cracks more deeply, does not require the use of organic chemical materials, has no negative impact on the environment, and requires low-priced materials. It has the advantages of simple operation, green environmental protection, high cost performance and good repair effect.
[0027] 3) The present invention utilizes microbial mineralization technology to bond natural zeolite to repair concrete cracks, which can effectively restore the bearing capacity, density and impermeability of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The unconfined compressive strength of concrete specimens with different vertical crack widths before and after repair;
[0029] Figure 2 is the propagation velocity of ultrasonic waves before and after the repair of concrete specimens with different vertical crack widths;
[0030] Figure 3 Capillary water absorption of concrete specimens with different vertical crack widths before and after repair;
[0031] Figure 4 Microscopic morphology of calcium carbonate generated for microbial remediation under vertical cracks;
[0032] Figure 5 This is the XRD pattern under vertical cracks. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0034] It should also be noted that, in order to avoid obscuring the technical solution of the present invention due to unnecessary details, only the technical solutions and / or processing steps closely related to the solution of the present invention are shown in the embodiments, while other details that are not very relevant are omitted.
[0035] This embodiment provides a method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite, comprising the following steps:
[0036] 1) Place a layer of plastic permeable gasket and permeable gauze on the concrete crack, and align the center of the circular grouting nozzle with the concrete crack;
[0037] 2) Glue the grouting nozzle to the concrete interface with waterproof glass glue;
[0038] 3) After the glass glue has dried for 20 to 40 hours, screw the glue injector on the top of the grouting nozzle, and use the pressure of the glue injector to inject natural zeolite particles into the cracks to fill the cracks; the particle size of the natural zeolite is 0.25 to 0.5 mm;
[0039] 4) Remove the glue injector, connect the peristaltic pump tube to the grouting nozzle, pump in the bacterial solution (the microorganism in the bacterial solution is Bacillus pasteurianus, which can induce the hydrolysis of urea to produce carbonate), wait for 2.5 to 7.5 hours, and then continue to inject the cementing liquid, where the cementing liquid is a mixed solution of urea and calcium acetate with equal concentration and volume, and its concentration is 0.25 mol / L to 1.5 mol / L. Then wait for 16 to 22 hours and repeat the grouting process. A total of 3 injections are made, and the amount of bacterial solution and cementing liquid pumped in each time is one-third of the crack volume.
[0040] The method for preparing the bacterial liquid comprises:
[0041] a) mixing 1000 mL of deionized water, 15-25 g of yeast extract, 10-20 g of ammonium sulfate, and 10-20 μmol of nickel chloride hexahydrate and stirring uniformly to prepare a microbial culture medium;
[0042] b) adding sodium hydroxide to the microbial culture medium to adjust its pH value to 10-12;
[0043] c) placing the microbial culture medium in an autoclave, sterilizing it at 130±8°C and 0.11-0.16MPa for 25-50 minutes, and then cooling it to room temperature;
[0044] d) using an inoculation loop to inoculate Bacillus pasteurianus into the sterilized microbial culture medium on a clean bench;
[0045] e) placing the inoculated microbial culture medium in a constant temperature shaking incubator, and continuously shaking and culturing at 20 to 30° C. and 200 to 230 rpm / min for 20 to 24 hours to obtain the bacterial solution.
[0046] The present invention uses homemade cracked concrete to test the concrete crack repair effect. The preparation method of the cracked concrete includes the following steps:
[0047] S1: Weigh cement, fly ash, sand, crushed stone, water and water reducing agent according to the proportion and mix and stir for 1 minute. Among them, cement is P·O42.5 grade ordinary Portland cement, fine aggregate is ordinary medium sand, coarse aggregate is crushed stone with continuous grading and particle size distribution of 5-25mm, fly ash is purchased from a company in Henan Province with grade I fly ash, calcium source is calcium acetate (analytical grade), water is ordinary tap water, water reducing agent is polycarboxylic acid water-based high-efficiency water reducing agent, and water reduction rate is 15-25%. The design strength grade of concrete is C30, the water-cement ratio is 0.45-0.55, the fly ash content is 35%-45%, and the water reducing agent content is 0.45%-0.55% of the cementitious material content;
[0048] S2: putting the mixture obtained in step S1 into a concrete test block mold;
[0049] S3: inserting a steel sheet with a thickness of 0.75 mm to 7.5 mm vertically into the concrete mixture to pre-embed the steel sheet, with an insertion depth of 25 to 50 mm;
[0050] S4: Place the mold with the pre-embedded steel sheet on a vibration table and vibrate for 0.5 min;
[0051] S5: Cover the surface of the poured complete concrete and concrete specimens with prefabricated cracks with a layer of plastic wrap, and then place them in a curing room at 20±2℃ and relative humidity not less than 95% for curing;
[0052] S6: After standing for 16 to 18 hours, pull out the steel sheet and continue curing;
[0053] S7: Remove the formwork after 30 to 40 hours and continue curing for 28 days.
[0054] Example 1
[0055] 1) Weigh cement, fly ash, sand, crushed stone, water and water reducing agent according to the proportion in Table 1 and mix and stir for 1 min. Among them, cement is P·O42.5 ordinary Portland cement, fine aggregate is ordinary medium sand, coarse aggregate is crushed stone with continuous grading and particle size distribution of 5-25mm, fly ash is purchased from a company in Henan Province, grade I fly ash, calcium source is calcium acetate (analytical grade), water is ordinary tap water, water reducing agent is polycarboxylic acid water-based high-efficiency water reducing agent, and water reduction rate is 25%.
[0056] Table 1 C30 concrete mix ratio
[0057]
[0058] 2) placing the mixture obtained in step 1) into a cubic concrete test block mold with a size of 100 mm×100 mm×100 mm;
[0059] 3) Insert a steel sheet with a thickness of 0.75 mm vertically into the concrete mixture to pre-embed the steel sheet, with an insertion depth of 50 mm;
[0060] 4) Place the mold with the pre-embedded steel sheet on a vibration table and vibrate for 0.5 minutes;
[0061] 5) Cover the surface of the poured complete concrete and concrete specimens with prefabricated cracks with a layer of plastic wrap, and then place them in a curing room at 20°C and a relative humidity of 95% for curing;
[0062] 6) After standing for 16 hours, pull out the steel sheet and continue curing;
[0063] 7) After 36 hours, remove the mold and continue to cure for 28 days;
[0064] 8) Place a layer of plastic permeable gasket and permeable gauze on the concrete crack, and align the center of the circular grouting nozzle with the concrete crack;
[0065] 9) Use waterproof glass glue to stick the grouting nozzle to the concrete interface;
[0066] 10) After the glass glue has dried for 24 hours, screw the glue injector on the top of the grouting nozzle, and use the pressure of the glue injector to inject natural zeolite particles with a particle size of 0.25-0.5mm into the crack to fill the crack;
[0067] 11) Remove the glue injector, connect the peristaltic pump tube to the grouting nozzle, pump in the bacterial solution, wait for 5 hours, and then continue to inject the cementing solution. Then wait for 19 hours and repeat the grouting process, for a total of 3 injections; the amount of bacterial solution and cementing solution pumped in each time is one-third of the crack volume (the cementing solution is a mixed solution of urea and calcium acetate with equal concentration and volume, and its concentration is 0.5 mol / L).
[0068] The microorganism in the bacterial solution is Bacillus pasteurianus that can induce calcium carbonate mineral deposition. The preparation method of the bacterial solution specifically comprises the following steps:
[0069] a) 1000 ml of deionized water, 20 g of yeast extract, 10 g of ammonium sulfate, and 10 μmol of nickel chloride hexahydrate were mixed and stirred uniformly to prepare a microbial culture medium;
[0070] b) adding sodium hydroxide to the microbial culture medium to adjust the pH value thereof to 11;
[0071] c) placing the microbial culture medium in an autoclave, sterilizing it at 121°C and 0.1 MPa for 35 minutes, and then cooling it to room temperature;
[0072] d) using an inoculation loop on a clean bench to inoculate Bacillus pasteurianus into the sterilized microbial culture medium;
[0073] e) placing the inoculated microbial culture medium in a constant temperature shaking incubator, and continuously shaking and culturing at 30° C. and 200 rpm / min for 20 to 24 hours to obtain a bacterial solution; wherein the OD600 (biomass) of the bacterial solution is about 4.0, and the urease activity is about 2.40 ms / (cm·min).
[0074] Comparative Example 1
[0075] The concrete sample preparation and repair process in this comparative example 1 are basically the same as those in Example 1, except that the repair process of step 8), step 9), step 10), and step 11) is cancelled, and a concrete test block with a surface crack width of 0.75 mm is directly used.
[0076] Example 2
[0077] The concrete sample preparation and repair process in Example 2 are basically the same as those in Example 1, except that the thickness of the steel sheet used in step 3) is 2 mm, and the width of the surface crack of the prepared concrete test block is 2 mm.
[0078] Comparative Example 2
[0079] The concrete sample preparation and repair process in this comparative example 2 are basically the same as those in Example 2, except that the repair process of step 8), step 9), step 10), and step 11) is cancelled, and the concrete test block with a surface crack width of 2 mm is directly used.
[0080] Example 3
[0081] The concrete sample preparation and repair process in this Example 3 are basically the same as those in Example 1, except that the thickness of the steel sheet used in step 3) is 4 mm, and the width of the surface crack of the prepared concrete test block is 4 mm.
[0082] Comparative Example 3
[0083] The concrete sample preparation and repair process in this comparative example 3 are basically the same as those in Example 3, except that the repair process of step 8), step 9), step 10), and step 11) is cancelled, and the concrete test block with a surface crack width of 4 mm is directly used.
[0084] Example 4
[0085] The concrete sample preparation and repair process in Example 4 are basically the same as those in Example 1, except that the thickness of the steel sheet used in step 3) is 7.5 mm, and the width of the surface crack of the prepared concrete test block is 7.5 mm.
[0086] Comparative Example 4
[0087] The concrete sample preparation and repair process in this comparative example 4 are basically the same as those in Example 4, except that the repair process of step 8), step 9), step 10), and step 11) is cancelled, and the concrete test block with a surface crack width of 7.5 mm is directly used.
[0088] Comparative Example 5
[0089] The concrete sample preparation and repair process in this comparative example 1 are basically the same as those in Example 1, except that no steel sheet pre-embedding is required when preparing the concrete test block, and the surface of the prepared concrete test block is intact and free of cracks.
[0090] Performance Testing
[0091] A comparative analysis was performed on the concrete test blocks with different crack widths repaired in the above Examples 1 to 4, the unrepaired concrete test blocks with different crack widths in Comparative Examples 1 to 5, and the intact concrete test blocks.
[0092] 1) Unconfined compressive strength analysis
[0093] The unconfined compressive strength of the intact concrete specimen is the highest, all cracks of different depths can be repaired and the unconfined compressive strength of the specimens is improved. As the crack width of the unrepaired specimen increases, the initial unconfined compressive strength of the concrete specimen decreases, and the greater the increase in the unconfined compressive strength after repair.
[0094] Perform unconfined compression test on the specimen: Figure 1 The unconfined compressive strength of the repaired concrete blocks with different crack widths is compared with that of the unrepaired concrete blocks with different crack widths.
[0095] Refer to the attached Figure 1As shown, the unconfined compressive strength of the intact concrete specimen is 46MPa. When the crack widths are 0.75mm, 2mm, 4mm, and 7.5mm, respectively, the unconfined compressive strengths of the unrepaired concrete specimens are 35.4MPa, 31.3MPa, 25.3MPa, and 20.7MPa, respectively. The unconfined compressive strengths of the repaired concrete specimens are 44.1MPa, 43.7MPa, 41.9MPa, and 40.6MPa, respectively, and the strength recovery rates are 95.8%, 95%, 91.1%, and 88.2%, respectively.
[0096] 2) Ultrasonic velocity analysis
[0097] Under the same crack width, as the number of grouting increases, the ultrasonic velocity increases, while the ultrasonic velocity increase gradually decreases. Under the same grouting number, as the crack width increases, the lower the ultrasonic velocity of the repaired sample, the lower the ultrasonic velocity recovery rate.
[0098] Ultrasonic velocity test of the sample: Figure 2 The comparison of the propagation speed of ultrasonic waves in the repaired concrete blocks with different crack widths and the unrepaired concrete blocks with different crack widths;
[0099] Refer to the attached Figure 2 As shown, the propagation speed of ultrasonic waves in intact concrete specimens is 3.204 km / s. When the crack widths are 0.75 mm, 2 mm, 4 mm, and 7.5 mm, respectively, the propagation speeds of ultrasonic waves in unrepaired concrete specimens are 2.639 km / s, 2.457 km / s, 2.32 km / s, and 2.05 km / s, respectively. The propagation speeds in repaired concrete specimens are 3.143 km / s, 3.122 km / s, 2.962 km / s, and 2.925 km / s, respectively. The repair rates are 99.3%, 99.1%, 97.8%, and 94.8%, respectively.
[0100] 3) Capillary water absorption analysis
[0101] Depend on Figure 3 It can be seen that after grouting three times with the same crack direction, the capillary water absorption rate gradually increases with the increase of crack width.
[0102] Test the capillary water absorption of the sample: Figure 3 Comparison of capillary water absorption in repaired concrete blocks with different crack widths, unrepaired concrete blocks with different crack widths and intact concrete blocks;
[0103] Refer to the attached Figure 3As shown, the capillary water absorption of the intact concrete specimen is 3.3%. When the crack widths are 0.75mm, 2mm, 4mm, and 7.5mm, respectively, the capillary water absorption of the unrepaired concrete specimen is 27.6%, 32.7%, 35.8%, and 40.7%, respectively; the capillary water absorption of the repaired concrete specimen is 4.0%, 4.3%, 5.5%, and 6.3%, respectively.
[0104] 4) Micromorphology analysis
[0105] The samples were analyzed by electron microscopy. Figure 4 As shown, Figure 4 This is the microscopic morphology of calcium carbonate induced by microorganisms, where a, b, and c are the top, middle, and bottom, respectively.
[0106] from Figure 4 It is not difficult to see that the calcium carbonate generated by using calcium acetate as the calcium source required for microbial remediation is mainly spherical calcium carbonate, the main component of which is vaterite. As the crack depth increases, the morphology of calcium carbonate crystals gradually changes from larger vaterite to more small granular calcium carbonate. The reason why the size of calcium carbonate changes with the depth of the crack may be that bacteria bind to Ca 2+ In the process, Ca in the cementing fluid 2+ The concentration gradually decreases, and as the depth of the crack increases, when the cementing fluid seeps to the bottom of the crack, it mainly produces small and irregularly shaped calcium carbonate crystals.
[0107] At the same time, calcium carbonate is mostly generated in the middle of the crack (such as Figure 4 This is because when the grouting method is used to repair concrete cracks, the top zeolite particles will be washed away by the cementing liquid, and most bacteria are not easy to attach to the upper part as the nucleation site of calcium carbonate. When the top of the zeolite particles is washed away, only a small number of bacteria attach to the surface of the zeolite particles to form ellipsoidal calcium carbonate (as shown in Figure 2). Figure 4 a), and some irregular needle-shaped calcium carbonate (such as Figure 4 As shown in a), the scouring effect in the middle of the zeolite particles is weakened, and a large number of bacteria attach to the surface of the particles as nucleation sites for calcium carbonate to generate a large number of spherical calcium carbonate.
[0108] A small amount of small particles of calcium carbonate and their stacked layers of calcium carbonate (such as Figure 4 c), but the amount of adhesion is significantly less than that in the middle. This is mainly because as the crack depth increases, the oxygen content decreases, and Bacillus pasteurianus, as an aerobic bacterium, stops its life activities after generating a small amount of calcium carbonate.
[0109] The method of using microbial mineralization technology to bond natural zeolite to repair concrete cracks can effectively fill the pores in the zeolite particles, improve their overall bonding ability, increase the overall density inside the concrete cracks, and thus restore the bearing capacity of the concrete structure.
[0110] 5) XRD analysis
[0111] The sample was subjected to X-ray diffraction analysis (XRD) and the results were as follows: Figure 5 shown.
[0112] Figure 5 This is the XRD spectrum under different crack directions. Figure 4 The calcium carbonate images captured in the image are all vaterite and a small amount of aragonite.
[0113] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite, characterized in that: The steps include: 1) Place a layer of plastic permeable gasket and permeable gauze on the concrete crack, and align the center of the circular grouting nozzle with the concrete crack; 2) Glue the grouting nozzle to the concrete interface with waterproof glass glue; 3) After the glass glue has dried for 20 to 40 hours, screw the glue injector on the top of the grouting nozzle, and use the pressure of the glue injector to inject the natural zeolite particles into the cracks to fill the cracks; 4) Remove the glue injector, connect the peristaltic pump tube to the grouting nozzle, pump in the bacterial solution, wait for 2.5 to 7.5 hours, and then continue to inject the cementing liquid. Then wait for 16 to 22 hours and repeat the grouting process. A total of 3 injections are made.
2. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 1, characterized in that: The particle size of the natural zeolite in step 3) is 0.25-0.5 mm.
3. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 1, characterized in that: The binder in step 4) is a mixed solution of urea and calcium acetate of equal concentration and volume, and its concentration is 0.25 mol / L to 1.5 mol / L.
4. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 1, characterized in that: The microorganism in the bacterial solution in step 4) is Bacillus pasteurianus, which can induce urea to hydrolyze and generate carbonate.
5. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 4, characterized in that: The method for preparing the bacterial liquid comprises: a) mixing deionized water, yeast extract, ammonium sulfate, and nickel chloride hexahydrate and stirring uniformly to prepare a microbial culture medium; b) adding sodium hydroxide to the microbial culture medium to adjust its pH value to 10-12; c) placing the microbial culture medium in an autoclave and cooling it to room temperature after sterilization; d) using an inoculation loop to inoculate Bacillus pasteurianus into the sterilized microbial culture medium on a clean bench; e) placing the inoculated microbial culture medium in a constant temperature shaking incubator, and shaking and culturing to obtain the bacterial solution.
6. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 5, characterized in that: In step a), 1000 mL of deionized water, 15-25 g of yeast extract, 10-20 g of ammonium sulfate, and 10-20 μmol of nickel chloride hexahydrate are mixed and stirred uniformly to prepare a microbial culture medium.
7. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 5, characterized in that: In step c), the microbial culture medium is sterilized at 130±8° C. and 0.11-0.16 MPa for 25-50 min and then cooled to room temperature.
8. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 5, characterized in that: The microbial culture medium inoculated in step e) is continuously shaken and cultured at 20-30° C. and 200-230 rpm / min for 20-24 hours to obtain the bacterial solution.
9. The method for repairing concrete cracks by using microbial mineralization technology to bond natural zeolite according to claim 1, characterized in that: In step 4), the amount of bacterial solution and cementing solution pumped in each time is one third of the fracture volume.